(untitled) (International Journal of Food and Nutritional Sciences, 2019)
The most famous painting method is fresco painting. It is renowned for being resilient and long-lasting against all environmental factors. Fresco paintings are put to wet lime-plaster using a mixture of dried mineral pigments and water as a medium